Drawing on social approval as a linguistic strategy: a discourse semantic analysis of judgement evaluation in suspected online romance scammer dating profiles - Lee, Kam-Fong; Chan, Mei Yuit; Mohamad Ali, Afida (Sciendo, 2024)
Online romance fraud is a crime carried out largely using language, as the victim and scammer typically do not meet in person in their entire interaction. As a language-enabled crime, a linguistic analysis of scam communication can shed light on how language is used to attract victims and influence their thoughts and actions. This study examined the first stage in the online scam strategy, that is, the putting up of a dating profile (user biography) on online dating service websites. The analysis employs the judgement evaluation framework of appraisal theory to examine the extent to which scammer profiles differ from a set of general user profiles in terms of their use of social approval as a linguistic strategy to attract a more compliant victim type. Findings from the study can help in raising public awareness about how linguistic resources are employed in luring potential victims in scammer dating profiles.